2014
DOI: 10.1016/j.jpeds.2014.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Common White Matter Microstructure Alterations in Pediatric Motor and Attention Disorders

Abstract: Our findings suggest that alterations in the corpus callosum underlie difficulties in motor and attention functioning. These changes are functionally and regionally distinct and could reflect a neurobiological basis for motor and attention disorders in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
111
2
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(131 citation statements)
references
References 44 publications
10
111
2
6
Order By: Relevance
“…Finally, several studies have reported no abnormalities in the cingulum bundle in patients with ADHD. [43][44][45] These discrepancies might be explained by variations in methodology and demographic characteristics (e.g., medication status, different comorbidities and subtypes) of participants. To minimize such confounding, the present study included only drugnaive patients with the combined ADHD type, and participants were carefully screened for comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, several studies have reported no abnormalities in the cingulum bundle in patients with ADHD. [43][44][45] These discrepancies might be explained by variations in methodology and demographic characteristics (e.g., medication status, different comorbidities and subtypes) of participants. To minimize such confounding, the present study included only drugnaive patients with the combined ADHD type, and participants were carefully screened for comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…Foram encontradas alterações no corpo caloso subjacentes às dificuldades motoras e atencionais, porém elas parecem ser regionalmente e funcionalmente distintas em cada transtorno. Anormalidades nas regiões frontais foram encontradas em crianças com TDAH, anormalidades em conexões na substância branca subjacentes ao córtex motor primário e somatossensorial foram exclusivas do TDC, enquanto que as crianças com TDAH e TDC demonstraram alterações em ambas as regiões calosas 32 . A coocorrência do TDAH e TDC foi associada com um padrão global distinto de diminuição da espessura cortical regional nas regiões fronto-temporal, parietal e occipital 32 .…”
Section: Bases Neurais Do Tdcunclassified
“…Achados de neuroimagem estrutural e funcional sugerem o envolvimento de redes cerebrais desenvolvimentalmente anormais relacionadas às funções de cognição, atenção e sensório-motoras tanto no TDAH quanto no TDC. As evidências que sustentam bases cerebrais comuns ainda são muito limitadas, mas os estudos em amostras bem definidos apontam para bases não compartilhadas para o TDAH e o TDC 32,59 . Comprometimentos em áreas cerebrais distintas podem ajudar a entender qual o tipo de problema motor é característi-co de cada transtorno, assim como da comorbidade.…”
Section: Implicações Clínicasunclassified
See 1 more Smart Citation
“…Recently, Langevin et al 4 found by means of MRI by diffusion tension images that some alterations in the Corpus callosum may underlie the difficulties in motor and attention functioning in children with ADHD and developmental motor disorder. In a second paper, Langevin and Ramdé showed that these changes may be seasonal, and shortening photoperiods contribute to increase the diurnal and nocturnal agitation of children with ADHD, and that lengthening diminish it 27 . Results from the above quoted research, support our data showing the possible pathophysiological basis of the motor alterations.…”
Section: Main Findingsmentioning
confidence: 99%